Sheath material for power storage devices, manufacturing method thereof, power storage device, and polyamide film
A laminate exterior material with a high-crystallization-index polyamide film and heat-fusible resin layer addresses the issues of shape diversity and damage resistance in power storage devices, enhancing their durability during removal.
Patent Information
- Application Number
- JP2024173898
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-09-26
- Filing Date
- 2024-10-02
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-05-18
AI Technical Summary
Conventional metal exterior materials for power storage devices are difficult to shape diversely, are heavy, and prone to damage when peeled off from products due to the application of large external forces during removal.
A laminate exterior material composed of a polyamide film with a crystallization index of 1.50 or more, a barrier layer, and a heat-fusible resin layer, designed to minimize damage during peeling by using a biaxially oriented nylon film as the base layer.
The laminate material effectively prevents damage to the exterior material of power storage devices when peeled off from a casing, ensuring the integrity and longevity of the device.
Smart Images

Figure 2025004096000007 
Figure 2025004096000008 
Figure 2025004096000009
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an exterior material for an electricity storage device, a manufacturing method thereof, an electricity storage device, and a polyamide film. [Background technology]
[0002] Conventionally, various types of electricity storage devices have been developed, and in all electricity storage devices, exterior materials are essential components for sealing electricity storage device elements such as electrodes, electrolytes, etc. Conventionally, metallic exterior materials have been widely used as exterior materials for electricity storage devices.
[0003] Meanwhile, in recent years, various shapes as well as thinner and lighter weight are required for electricity storage devices along with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc. However, the metallic exterior materials for electricity storage devices that have been widely used in the past have the drawbacks of being difficult to keep up with the diversification of shapes and also having limitations in terms of weight reduction.
[0004] In recent years, a film-like laminate in which a base layer, a barrier layer, and a heat-sealable resin layer are laminated in this order has been proposed as an exterior material for an electricity storage device that can be easily processed into a variety of shapes and can be made thinner and lighter (see, for example, Patent Document 1).
[0005] In such an exterior material for an electricity storage device, a recess is generally formed by cold forming, and electricity storage device elements such as electrodes and an electrolyte are placed in the space formed by the recess, and the heat-sealable resin layer is then heat-sealed to obtain an electricity storage device in which the electricity storage device elements are housed inside the exterior material for an electricity storage device. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2008-287971 A Summary of the Invention [Problem to be solved by the invention]
[0007] Electricity storage device elements contain components such as rare metals, and the demand for these components is rapidly increasing. For this reason, when replacing an electricity storage device in various products such as electrical equipment, there is a demand to remove the device from the product and recover and reuse the various components contained in the electricity storage device element.
[0008] In various products such as electrical equipment, the electricity storage device is firmly fixed to the housing of the product by double-sided tape, adhesive, or the like. Therefore, when the electricity storage device is removed from the housing of the product, a large external force is applied to the electricity storage device. Specifically, the electricity storage device is generally removed from the housing using a metal spatula or the like, and a large external force is applied to the electricity storage device. If a large external force is applied to an exterior material for an electricity storage device made of a film-like laminate when removing the electricity storage device, there is a risk that the exterior material for an electricity storage device will be damaged.
[0009] Under these circumstances, a main objective of the present disclosure is to provide an exterior material for an electricity storage device that is suppressed from being damaged when an electricity storage device fixed to a housing with double-sided tape or the like is peeled off from the housing. [Means for solving the problem]
[0010] The inventors of the present disclosure conducted intensive studies to solve the above-mentioned problems. As a result, they found that an exterior material for an electricity storage device, which is composed of a laminate including, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, the base layer includes a polyamide film, and the crystallization index of the polyamide film measured from the outside of the base layer by the ATR method of Fourier transform infrared spectroscopy is a predetermined value or more, is suppressed from being damaged when the electricity storage device fixed to the housing with double-sided tape or the like is peeled off from the housing.
[0011] The present disclosure has been completed based on these findings and through further investigations. That is, the present disclosure provides the invention of the following aspects. The laminate includes, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, The substrate layer includes a polyamide film, An exterior material for an electricity storage device, wherein the polyamide film has a crystallization index of 1.50 or more as measured from the outside of the base layer by an ATR method of Fourier transform infrared spectroscopy. Effect of the Invention
[0012] According to the present disclosure, it is possible to provide an exterior material for an electricity storage device that is suppressed from being damaged when an electricity storage device fixed to a housing with double-sided tape or the like is peeled off from the housing with a metal spatula, etc. According to the present disclosure, it is also possible to provide a manufacturing method for the exterior material for an electricity storage device, an electricity storage device using the exterior material for an electricity storage device, and a polyamide film suitable for use as a base layer of the exterior material for an electricity storage device. [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 2] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 3] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Figure 4] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 5] 4A to 4C are schematic diagrams illustrating a procedure for producing a sample used in a peel test of an electricity storage device in an example. [Figure 6] 3A and 3B are a side view and a plan view of a sample used in a peel test of an electricity storage device in the examples. [Figure 7]1A is a side view and FIG. 1B is a plan view of a double-sided tape attached to a sample used in a peel test of an electricity storage device in an example. [Figure 8] FIG. 2 is a schematic diagram showing how an electricity storage device is peeled off from a stainless steel plate using a metal spoon in a peel test of the electricity storage device in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The exterior material for an electricity storage device of the present disclosure is composed of a laminate including, in order from the outside, at least a base material layer, a barrier layer, and a heat-sealable resin layer, the base material layer includes a polyamide film, and the polyamide film has a crystallization index of 1.50 or more measured from the outside of the base material layer by an ATR method of Fourier transform infrared spectroscopy. The exterior material for an electricity storage device of the present disclosure is suppressed from being damaged when an electricity storage device fixed to a housing with double-sided tape or the like is peeled off from the housing.
[0015] The exterior material for an electricity storage device according to the present disclosure will be described in detail below. In this specification, the numerical range indicated by "to" means "not less than" or "not more than." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.
[0016] 1.Layer structure and physical properties of exterior materials for energy storage devices The exterior material 10 for an electricity storage device according to the present disclosure is composed of a laminate including, in order from the outside, a base layer 1, a barrier layer 3, and a heat-sealable resin layer 4, as shown in FIG. 1 for example. In the exterior material 10 for an electricity storage device, the base layer 1 is the outermost layer, and the heat-sealable resin layer 4 is the innermost layer. When assembling an electricity storage device using the exterior material 10 for an electricity storage device and an electricity storage device element, the heat-sealable resin layers 4 of the exterior material 10 for an electricity storage device are placed opposite each other, and the electricity storage device element is accommodated in a space formed by heat-sealing the periphery. In the laminate constituting the exterior material 10 for an electricity storage device according to the present disclosure, the barrier layer 3 is used as a reference, and the heat-sealable resin layer 4 side is on the inner side relative to the barrier layer 3, and the base layer 1 side is on the outer side relative to the barrier layer 3.
[0017] As shown in Figures 2 to 4, for example, the exterior material 10 for an electricity storage device may have an adhesive layer 2 between the base material layer 1 and the barrier layer 3, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figures 3 and 4, for example, the exterior material 10 for an electricity storage device may have an adhesive layer 5 between the barrier layer 3 and the heat-sealable resin layer 4, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figure 5, a surface coating layer 6 or the like may be provided on the outer side of the base material layer 1 (the side opposite to the heat-sealable resin layer 4 side) if necessary.
[0018] The thickness of the laminate constituting the exterior material 10 for an electricity storage device is not particularly limited, but the upper limit, from the viewpoints of cost reduction, improving energy density, etc., is preferably about 180 μm or less, about 155 μm or less, or about 120 μm or less, and the lower limit, from the viewpoint of maintaining the function of the exterior material for an electricity storage device of protecting the electricity storage device elements, is preferably about 35 μm or more, about 45 μm or more, or about 60 μm or more, and preferred ranges include, for example, about 35 to 180 μm, about 35 to 155 μm, about 35 to 120 μm, about 45 to 180 μm, about 45 to 155 μm, about 45 to 120 μm, about 60 to 180 μm, about 60 to 155 μm, or about 60 to 120 μm, and of these, 60 to 120 μm is particularly preferred.
[0019] In the exterior material 10 for an electricity storage device, the ratio of the total thickness of the base material layer 1, the adhesive layer 2 provided as needed, the barrier layer 3, the adhesive layer 5 provided as needed, the heat-sealable resin layer 4, and the surface coating layer 6 provided as needed to the thickness (total thickness) of the laminate constituting the exterior material 10 for an electricity storage device is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more. As a specific example, when the exterior material 10 for an electricity storage device of the present disclosure includes the base material layer 1, the adhesive layer 2, the barrier layer 3, the adhesive layer 5, and the heat-sealable resin layer 4, the ratio of the total thickness of these layers to the thickness (total thickness) of the laminate constituting the exterior material 10 for an electricity storage device is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more.
[0020] The base material layer 1 of the exterior material 10 for an electricity storage device of the present disclosure contains a polyamide film, and the crystallization index of the polyamide film measured from the outside of the base material layer 1 by the ATR method of Fourier transform infrared spectroscopy is 1.50 or more. The method for measuring the crystallization index of the base material layer 1 of the exterior material 10 for an electricity storage device of the present disclosure is as follows.
[0021] <Measurement of the crystallization index of the base material layer of the exterior material for power storage devices> The exterior material for a power storage device is cut into a 100 mm × 100 mm square to prepare a sample. The surface of the polyamide film located on the outside of the obtained sample is subjected to infrared absorption spectrum measurement in an environment of a temperature of 25°C and a relative humidity of 50% using the ATR measurement mode of FT-IR. As an apparatus, for example, Nicolet iS10 manufactured by Thermo Fisher Scientific Co., Ltd. can be used. From the obtained absorption spectrum, a 1200 cm -1 The peak intensity P near the center and the absorption unrelated to the crystal 1370cm comes from -1The peak intensity Q near the peak intensity P is measured, and the intensity ratio X=P / Q of the peak intensity P to the peak intensity Q is calculated as the crystallization index. When obtaining an exterior material for an electricity storage device from an electricity storage device to measure the crystallization index of the base material layer, the exterior material for an electricity storage device is obtained from the top or bottom surface, not from the heat-sealed portion or side surface, of the electricity storage device to prepare a sample. (Measurement conditions) Method: Macro ATR method Wavenumber resolution: 8cm -1 Number of times: 32 Detector: DTGS detector ATR prism: Ge Incident angle: 45° Baseline: Wave number 1100cm -1 From 1400cm -1 The curve was calculated as a straight line approximation between the two. Absorption peak intensity Y 1200 : Wave number 1195cm -1 From 1205cm -1 The maximum peak intensity in the range minus the baseline value Absorption peak intensity Y 1370 : Wave number 1365cm -1 From 1375cm -1 The maximum peak intensity in the range minus the baseline value
[0022] When the outer surface of the electricity storage device exterior material 10 is made of the polyamide film of the base material layer 1, the crystallization index can be measured directly for the electricity storage device exterior material 10. When the outer surface of the electricity storage device exterior material 10 is not made of the polyamide film of the base material layer 1, such as when the base material layer 1 has a multilayer structure as described below and a resin film (e.g., a polyester film) different from the polyamide film is positioned outside the polyamide film, or when a surface coating layer 6 described below is laminated on the outside of the base material layer 1, the crystallization index can be measured by removing the layer positioned outside the polyamide film from the electricity storage device exterior material 10 to expose the surface of the polyamide film.
[0023] In the electrical storage device packaging material 10, the crystallization index may be 1.50 or more, but from the viewpoint of more effectively suppressing damage to the electrical storage device packaging material during the above-mentioned peeling, it is more preferably 1.55 or more, even more preferably 1.60 or more, and particularly preferably 1.65 or more. The upper limit of the crystallization index is not particularly limited, and examples thereof include 2.50 or less and 1.80 or less. Preferred ranges of the crystallization index include, for example, 1.50 to 2.50, 1.60 to 2.50, 1.65 to 2.50, 1.50 to 1.80, 1.60 to 1.80, and 1.65 to 1.80.
[0024] Methods for increasing the crystallization index of the polyamide film contained in the base material layer 1 of the exterior material 10 for an electricity storage device to 1.50 or more include methods for promoting crystallization (promoting the production of α crystals) by adjusting the stretching ratio, heat setting temperature, and further the post-heating temperature and time during the production process of the polyamide film.
[0025] 2. Each layer that forms the exterior material for electricity storage devices [Base material layer 1] In the present disclosure, the substrate layer 1 is a layer provided for the purpose of exhibiting the function as a substrate of the exterior material for an electricity storage device, etc. The substrate layer 1 is located on the outer layer side of the exterior material for an electricity storage device.
[0026] The base layer 1 includes a polyamide film. As described above, the crystallization index of the polyamide film measured from the outside of the base layer 1 by the ATR method of Fourier transform infrared spectroscopy is 1.50 or more.
[0027] The polyamide forming the polyamide film may be any polyamide having α crystals, and specifically includes aliphatic polyamides such as nylon 6, nylon 66, nylon 46, and a copolymer of nylon 6 and nylon 66. These polyamides may be used alone or in combination of two or more. The polyamide film is preferably a nylon film.
[0028] The polyamide film may be an unstretched film or a stretched film. When the base material layer 1 includes an unstretched film, when laminating each layer of the exterior material 10 for a power storage device, the unstretched film may be extruded to form an unstretched film, a previously prepared unstretched film may be bonded, or a resin (polyamide) may be applied to form an unstretched film. Examples of a method for applying a resin include a roll coating method, a gravure coating method, and an extrusion coating method. When the base material layer 1 is a stretched film, a previously prepared stretched film is bonded when laminating each layer of the exterior material 10 for a power storage device. Examples of the stretched film include a uniaxially stretched film and a biaxially stretched film, and a biaxially stretched film is preferable. Examples of a stretching method for forming a biaxially stretched film include a sequential biaxial stretching method, an inflation method, and a simultaneous biaxial stretching method.
[0029] The polyamide film is preferably a biaxially oriented nylon film.
[0030] The exterior material 10 for an electric storage device according to the present disclosure can be manufactured using a polyamide film having a crystallization index of 1.50 or more measured by the ATR method of Fourier transform infrared spectroscopy as the base material layer 1, or the crystallization index can be increased to 1.50 or more by applying heat to the polyamide film during the manufacturing process of the exterior material 10 for an electric storage device. As described later in the section "5. Polyamide film", the exterior material 10 for an electric storage device according to the present disclosure is preferably manufactured using a polyamide film having a crystallization index of 1.50 or more measured by the ATR method of Fourier transform infrared spectroscopy as the base material layer 1. That is, the exterior material 10 for an electric storage device according to the present disclosure is preferably manufactured by using a polyamide film having a crystallization index of 1.50 or more measured by the ATR method of Fourier transform infrared spectroscopy as the base material layer 1, and laminating it with each layer such as the barrier layer 3 and the heat-sealable resin layer 4. Furthermore, as shown in the examples described later, the crystallization index of the polyamide film laminated to the exterior packaging material 10 for an electricity storage device and contained in the base material layer 1 can be made higher than that of the polyamide film before it is applied to the exterior packaging material 10 for an electricity storage device.
[0031] The thickness of the polyamide film is, from the viewpoint of more effectively preventing damage to the exterior material for an electricity storage device during the aforementioned peeling, preferably about 3 μm or more, more preferably about 10 μm or more, and is also preferably about 50 μm or less, more preferably about 35 μm or less. Preferred ranges include about 3 to 50 μm, about 3 to 35 μm, about 10 to 50 μm, and about 10 to 35 μm, and of these, about 10 to 35 μm is particularly preferred.
[0032] The substrate layer 1 may further have a resin film different from the polyamide film. Examples of resins forming a resin film different from the polyamide film include polyester, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin, and other resins, and modified products of these resins. The resin may be a copolymer of these resins or a modified product of the copolymer. Furthermore, it may be a mixture of these resins. Among these, polyester is preferable.
[0033] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters. Examples of copolymerized polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit. Specific examples of polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit and is polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), and polyethylene (terephthalate / decane dicarboxylate). These polyesters may be used alone or in combination of two or more. Among these, polyethylene terephthalate and polybutylene terephthalate are preferred.
[0034] The polyester film is preferably a stretched polyester film, more preferably a biaxially stretched polyester film.
[0035] The polyester film is preferably a biaxially oriented polyethylene terephthalate film or a biaxially oriented polybutylene terephthalate film.
[0036] When the base layer 1 further has a resin film other than the polyamide film, the thickness of the other resin film is not particularly limited as long as it does not impair the effects of the present invention, and is preferably about 3 μm or more, more preferably about 10 μm or more, and is preferably about 50 μm or less, more preferably about 35 μm or less. Preferred ranges include about 3 to 50 μm, about 3 to 35 μm, about 10 to 50 μm, and about 10 to 35 μm, and of these, about 10 to 35 μm is particularly preferred.
[0037] The base material layer 1 may be a single layer or may be composed of two or more layers as long as it contains a polyamide film, and from the viewpoint of making the exterior material 10 for an electricity storage device thinner, it is preferably a single layer of polyamide film.
[0038] When the base layer 1 is composed of two or more layers, the base layer 1 may be a laminate in which resin films are laminated with an adhesive or the like, or a laminate of resin films formed by co-extruding resins into two or more layers. In addition, a laminate of resin films formed by co-extruding resins into two or more layers may be used as the base layer 1 as is, or may be uniaxially or biaxially stretched to form the base layer 1.
[0039] In the substrate layer 1, specific examples of the laminate of two or more resin films include a laminate of a polyester film and a nylon film, a laminate of two or more nylon films, etc., and preferably a laminate of a stretched nylon film and a stretched polyester film, or a laminate of two or more stretched nylon films. For example, when the substrate layer 1 is a laminate of two resin films, a laminate of a polyamide resin film and a polyamide resin film, or a laminate of a polyester resin film and a polyamide resin film, is preferred, and a laminate of a nylon film and a nylon film, or a laminate of a polyethylene terephthalate film and a nylon film, is more preferred. In addition, when the substrate layer 1 is a laminate of two or more resin films, it is preferred that the polyester resin film is located in the outermost layer of the substrate layer 1, because the polyester resin is less likely to discolor when, for example, an electrolyte is attached to the surface.
[0040] When the base layer 1 is a laminate of two or more resin films, the two or more resin films may be laminated via an adhesive. Preferred adhesives include the same adhesives as those exemplified in the adhesive layer 2 described later. The method for laminating two or more resin films is not particularly limited, and known methods can be adopted, such as dry lamination, sandwich lamination, extrusion lamination, and thermal lamination, and preferably dry lamination. When laminating by the dry lamination method, it is preferable to use a polyurethane adhesive as the adhesive. In this case, the thickness of the adhesive is, for example, about 2 to 5 μm. Also, an anchor coat layer may be formed on the resin film and laminated. The anchor coat layer may be the same adhesive as that exemplified in the adhesive layer 2 described later. In this case, the thickness of the anchor coat layer is, for example, about 0.01 to 1.0 μm.
[0041] Furthermore, additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present on at least one of the surface and the interior of the base layer 1. The additives may be used alone or in combination of two or more.
[0042] In the present disclosure, from the viewpoint of improving the moldability of the exterior material for a power storage device, it is preferable that a lubricant is present on the surface of the base material layer 1. The lubricant is not particularly limited, but is preferably an amide-based lubricant. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleic acid amide, etc. Examples of the fatty acid ester amide include stearamide ethyl stearate. Examples of the aromatic bisamide include m-xylylene bisstearamide, m-xylylene bishydroxystearamide, and N,N'-distearylisophthalamide. The lubricant may be used alone or in combination of two or more.
[0043] When a lubricant is present on the surface of the base layer 1, the amount of the lubricant is not particularly limited, but is preferably about 3 mg / m 2 More preferably, 4 to 15 mg / m 2 about 5 to 14 mg / m 2 The degree of
[0044] The lubricant present on the surface of the base layer 1 may be a lubricant exuded from the resin constituting the base layer 1, or a lubricant applied to the surface of the base layer 1.
[0045] The total thickness of the substrate layer 1 is not particularly limited as long as it functions as a substrate, and is, for example, about 3 to 50 μm, and preferably about 10 to 35 μm.
[0046] [Coat layer] The exterior material for an electric storage device according to the present disclosure may have a coating layer (not shown) on the substrate layer 1 (the side opposite to the barrier layer 3 of the substrate layer 1) as necessary for the purpose of improving printability, moldability, and the like. The coating layer is provided so as to be in contact with the substrate layer 1. The thickness of the coating layer is not particularly limited as long as it exhibits the above-mentioned function as a coating layer, and may be, for example, about 0.01 to 0.40 μm, preferably about 0.01 to 0.30 μm, and more preferably about 0.1 to 0.30 μm. By having a thickness of 0.01 μm or more, a layer with a uniform film thickness can be formed on the substrate layer 1. As a result, the printability of the exterior material for an electric storage device according to the present disclosure does not become uneven, making it possible to perform uniform printing, and uniform moldability can be obtained.
[0047] Examples of resins that form the coating layer include various synthetic resins such as polyvinylidene chloride, vinylidene chloride-vinyl chloride copolymer, polyolefin, acid-modified polyolefin, polyester, epoxy resin, phenolic resin, fluororesin, cellulose ester, polyurethane, acrylic resin, polyamide, etc. Among these, polyurethane, polyester, and acrylic resin are preferred.
[0048] The coating layer may contain lubricants and additives as necessary to improve the slipperiness. Examples of the lubricants include the same lubricants as those described above. Examples of the additives include the same additives as those exemplified in the surface coating layer 6 described below. The content and particle size of these lubricants and additives are appropriately adjusted according to the thickness of the coating layer.
[0049] In addition, the exterior material for a power storage device of the present disclosure may have a coating layer (not shown) on one side (the barrier layer 3 side of the substrate layer 1 or the side opposite to the barrier layer 3 of the substrate layer 1) or both sides of the substrate layer 1, as necessary, for the purpose of improving adhesion to the layer adjacent to the substrate layer. That is, the coating layer provided on the substrate layer may be a layer intended to improve printability, formability, etc., or may be a layer intended to improve the adhesiveness of the substrate layer. Even when the coating layer is intended to improve the adhesiveness of the substrate layer, the resin forming the coating layer and the thickness are exemplified by the same resins and thicknesses as those of the coating layer described above. In addition, the above-mentioned lubricants and additives may be included, but when there is an adjacent layer on the opposite side of the substrate layer to the coating layer, it is preferable not to include lubricants or additives.
[0050] [Adhesive layer 2] In the exterior material for an electricity storage device of the present disclosure, the adhesive layer 2 is a layer that is provided between the base layer 1 and the barrier layer 3 as necessary for the purpose of increasing the adhesion between them.
[0051] The adhesive layer 2 is formed of an adhesive capable of bonding the base material layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 is not limited, and may be any of a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressure type, etc. Also, it may be a two-component curing adhesive (two-component adhesive), a one-component curing adhesive (one-component adhesive), or a resin that does not involve a curing reaction. Also, the adhesive layer 2 may be a single layer or multiple layers.
[0052] Specific examples of adhesive components contained in the adhesive include polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolymerized polyamides; polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth)acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferred. In addition, the adhesive strength of these adhesive component resins can be increased by using an appropriate curing agent in combination. The curing agent is selected from polyisocyanates, multifunctional epoxy resins, oxazoline group-containing polymers, polyamine resins, acid anhydrides, and the like, depending on the functional groups of the adhesive components.
[0053] Examples of polyurethane adhesives include polyurethane adhesives containing a base agent containing a polyol compound and a curing agent containing an isocyanate compound. Preferably, a two-component curing polyurethane adhesive is used in which a polyol such as polyester polyol, polyether polyol, or acrylic polyol is used as a base agent and an aromatic or aliphatic polyisocyanate is used as a curing agent. In addition, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the terminal hydroxyl group of the repeating unit as the polyol compound. Since the adhesive layer 2 is formed from a polyurethane adhesive, the exterior material for the electricity storage device is given excellent electrolyte resistance, and the base layer 1 is prevented from peeling off even if the electrolyte adheres to the side surface.
[0054] In addition, the adhesive layer 2 is allowed to contain other components as long as they do not impair adhesion, and may contain a colorant, a thermoplastic elastomer, a tackifier, a filler, etc. By containing a colorant in the adhesive layer 2, the exterior material for a power storage device can be colored. As the colorant, known colorants such as pigments and dyes can be used. In addition, only one type of colorant may be used, or two or more types may be mixed and used.
[0055] The type of pigment is not particularly limited as long as it does not impair the adhesiveness of the adhesive layer 2. Examples of organic pigments include azo-based, phthalocyanine-based, quinacridone-based, anthraquinone-based, dioxazine-based, indigothioindigo-based, perinone-perylene-based, isoindolenine-based, and benzimidazolone-based pigments, and examples of inorganic pigments include carbon black-based, titanium oxide-based, cadmium-based, lead-based, chromium oxide-based, iron-based, and copper-based pigments, and other pigments include fine powder of mica and fish scale foil. Pigments can be used alone or in combination of two or more types, for example, a mixture of an organic pigment and an inorganic pigment may be used.
[0056] Among colorants, carbon black is preferred in order to give the exterior material for an electricity storage device a black appearance, for example.
[0057] The average particle size of the pigment is not particularly limited and may be, for example, about 0.05 to 5 μm, and preferably about 0.08 to 2 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0058] The content of the pigment in the adhesive layer 2 is not particularly limited as long as the exterior material for an electricity storage device is colored, and is, for example, about 5 to 60 mass %, preferably 8 to 40 mass %.
[0059] The thickness of the adhesive layer 2 is not particularly limited as long as it can bond the base layer 1 and the barrier layer 3, but the lower limit is, for example, about 1 μm or more, about 2 μm or more, and the upper limit is about 10 μm or less, about 5 μm or less, and preferred ranges are about 1 to 10 μm, about 1 to 5 μm, about 2 to 10 μm, and about 2 to 5 μm.
[0060] [Colored layer] The colored layer is a layer that is provided between the base material layer 1 and the barrier layer 3 as necessary (not shown). When the adhesive layer 2 is provided, a colored layer may be provided between the base material layer 1 and the adhesive layer 2, or between the adhesive layer 2 and the barrier layer 3. Also, a colored layer may be provided on the outside of the base material layer 1. By providing a colored layer, the exterior material for an electricity storage device can be colored.
[0061] The colored layer can be formed, for example, by applying an ink containing a colorant to the surface of the base layer 1, the surface of the adhesive layer 2, or the surface of the barrier layer 3. As the colorant, known substances such as pigments and dyes can be used. Furthermore, only one type of colorant may be used, or two or more types may be mixed together.
[0062] Specific examples of the colorant contained in the colored layer include the same as those exemplified in the section [Adhesive layer 2].
[0063] [Barrier layer 3] In the packaging material for an electricity storage device, the barrier layer 3 is a layer that at least prevents the penetration of moisture.
[0064] Examples of the barrier layer 3 include metal foils, vapor-deposited films, and resin layers having barrier properties. Examples of the vapor-deposited films include metal vapor-deposited films, inorganic oxide vapor-deposited films, and carbon-containing inorganic oxide vapor-deposited films. Examples of the resin layer include fluorine-containing resins such as polyvinylidene chloride, polymers mainly composed of chlorotrifluoroethylene (CTFE), polymers mainly composed of tetrafluoroethylene (TFE), polymers having fluoroalkyl groups, and polymers mainly composed of fluoroalkyl units, and ethylene-vinyl alcohol copolymers. Examples of the barrier layer 3 include resin films having at least one of these vapor-deposited films and resin layers. The barrier layer 3 may be provided in a plurality of layers. The barrier layer 3 preferably includes a layer made of a metal material. Specific examples of the metal material constituting the barrier layer 3 include aluminum alloys, stainless steel, titanium steel, and steel plates. When used as a metal foil, it is preferable to include at least one of aluminum alloy foil and stainless steel foil.
[0065] From the viewpoint of improving the formability of the exterior material for a power storage device, the aluminum alloy foil is preferably a soft aluminum alloy foil made of, for example, an annealed aluminum alloy, and from the viewpoint of further improving the formability, the aluminum alloy foil is preferably an iron-containing aluminum alloy foil. In the iron-containing aluminum alloy foil (100 mass%), the iron content is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%. By making the iron content 0.1 mass% or more, an exterior material for a power storage device having better formability can be obtained. By making the iron content 9.0 mass% or less, an exterior material for a power storage device having better flexibility can be obtained. Examples of the soft aluminum alloy foil include aluminum alloy foils having a composition specified in JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, or JIS H4000:2014 A8079P-O. Silicon, magnesium, copper, manganese, etc. may be added as necessary. Softening can be performed by annealing or the like.
[0066] Examples of the stainless steel foil include austenitic, ferritic, austenitic-ferritic, martensitic, and precipitation hardened stainless steel foils. From the viewpoint of providing an exterior material for an electricity storage device having excellent formability, the stainless steel foil is preferably made of austenitic stainless steel.
[0067] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L, and among these, SUS304 is particularly preferred.
[0068] When the barrier layer 3 is a metal foil, it is sufficient that the barrier layer 3 has a thickness that at least functions as a barrier layer that prevents the intrusion of moisture, and the thickness is, for example, about 9 to 200 μm. The thickness of the barrier layer 3 is, for example, preferably about 85 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, and particularly preferably about 35 μm or less, and preferably about 10 μm or more, more preferably about 20 μm or more, and more preferably about 25 μm or more, with the thickness being preferably in the range of about 10 to 85 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 35 μm, about 20 to 85 μm, about 20 to 50 μm, about 20 to 40 μm, about 20 to 35 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 40 μm, and about 25 to 35 μm, and among these, about 25 to 40 μm is particularly preferred. When the barrier layer 3 is made of an aluminum alloy foil, the above-mentioned range is particularly preferred. In particular, when the barrier layer 3 is composed of a stainless steel foil, the upper limit of the thickness of the stainless steel foil is preferably about 60 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, even more preferably about 30 μm or less, and particularly preferably about 25 μm or less, and the lower limit is preferably about 10 μm or more, more preferably about 15 μm or more. Preferred thickness ranges include about 10 to 60 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, about 10 to 25 μm, about 15 to 60 μm, about 15 to 50 μm, about 15 to 40 μm, about 15 to 30 μm, and about 15 to 25 μm.
[0069] In addition, when the barrier layer 3 is a metal foil, it is preferable to provide a corrosion-resistant film at least on the surface opposite to the base layer in order to prevent dissolution and corrosion. The barrier layer 3 may have a corrosion-resistant film on both sides. Here, the corrosion-resistant film refers to a thin film that is provided with corrosion resistance by performing, for example, hydrothermal conversion treatment such as boehmite treatment, chemical conversion treatment, anodizing treatment, plating treatment such as nickel or chromium, or corrosion prevention treatment by applying a coating agent on the surface of the barrier layer. As a treatment for forming a corrosion-resistant film, one type may be performed, or two or more types may be combined. In addition to one layer, multiple layers can be formed. Furthermore, among these treatments, hydrothermal conversion treatment and anodizing treatment are treatments in which the metal foil surface is dissolved by a treatment agent to form a metal compound having excellent corrosion resistance. Note that these treatments may be included in the definition of chemical conversion treatment. In addition, when the barrier layer 3 has a corrosion-resistant film, the barrier layer 3 includes the corrosion-resistant film.
[0070] The corrosion-resistant coating prevents delamination between a barrier layer (e.g., an aluminum alloy foil) and a base layer during molding of an exterior material for an electricity storage device, prevents dissolution and corrosion of the barrier layer surface due to hydrogen fluoride produced by a reaction between an electrolyte and moisture, and in particular prevents dissolution and corrosion of aluminum oxide present on the barrier layer surface when the barrier layer is an aluminum alloy foil, and also improves the adhesion (wettability) of the barrier layer surface, thereby preventing delamination between the base layer and the barrier layer during heat sealing and between the base layer and the barrier layer during molding.
[0071] Various corrosion-resistant films formed by chemical conversion treatments are known, and mainly include corrosion-resistant films containing at least one of phosphates, chromates, fluorides, triazine thiol compounds, and rare earth oxides. Examples of chemical conversion treatments using phosphates and chromates include chromate chromate treatment, phosphoric acid chromate treatment, phosphoric acid-chromate treatment, and chromate treatment. Examples of chromium compounds used in these treatments include chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate. Examples of phosphorus compounds used in these treatments include sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid. Examples of chromate treatments include etching chromate treatment, electrolytic chromate treatment, and coating-type chromate treatment, and coating-type chromate treatment is preferred. In this coating type chromate treatment, at least the inner layer side of the barrier layer (e.g., aluminum alloy foil) is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is coated with a treatment liquid mainly composed of a metal phosphate such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, or Zn (zinc) phosphate, or a mixture of these metal salts, or a treatment liquid mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid consisting of a mixture of these with a synthetic resin, or the like, by a known coating method such as a roll coating method, a gravure printing method, or a dipping method, and then dried. As the treatment liquid, various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents can be used, and water is preferred. Examples of the resin component used here include polymers such as phenolic resins and acrylic resins, and chromate treatment using an aminated phenol polymer having repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.The acrylic resin is preferably polyacrylic acid, acrylic acid methacrylic acid ester copolymer, acrylic acid maleic acid copolymer, acrylic acid styrene copolymer, or a derivative thereof such as sodium salt, ammonium salt, or amine salt. In particular, a derivative of polyacrylic acid such as an ammonium salt, sodium salt, or amine salt of polyacrylic acid is preferable. In the present disclosure, polyacrylic acid means a polymer of acrylic acid. The acrylic resin is also preferably a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride, and is also preferably an ammonium salt, sodium salt, or amine salt of a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride. Only one type of acrylic resin may be used, or two or more types may be mixed and used.
[0072] [ka]
[0073] [ka]
[0074] [ka]
[0075] [ka]
[0076] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxy group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each independently represent a hydroxy group, an alkyl group, or a hydroxyalkyl group. 1 and R 2Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) to (4) include linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group represented by the following formulae may be the same or different. In the general formulae (1) to (4), X is preferably a hydrogen atom, a hydroxy group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the general formulae (1) to (4) is preferably about 500 to 1,000,000, for example, and more preferably about 1,000 to 20,000. The aminated phenol polymer can be prepared, for example, by polycondensing a phenol compound or a naphthol compound with formaldehyde to produce a polymer consisting of the repeating units represented by the above general formula (1) or (3), and then polycondensing the polymer with formaldehyde and an amine (R 1 R 2 NH) to the functional group (-CHNR 1 R 2 ) into the polymer obtained above. The aminated phenol polymers may be used alone or in combination of two or more.
[0077] Another example of the corrosion-resistant film is a thin film formed by a coating-type corrosion prevention treatment in which a coating agent containing at least one selected from the group consisting of rare earth element oxide sol, anionic polymer, and cationic polymer is applied. The coating agent may further contain phosphoric acid or a phosphate, and a crosslinking agent for crosslinking the polymer. The rare earth element oxide sol has rare earth element oxide fine particles (for example, particles with an average particle size of 100 nm or less) dispersed in a liquid dispersion medium. Examples of rare earth element oxides include cerium oxide, yttrium oxide, neodymium oxide, and lanthanum oxide, and cerium oxide is preferred from the viewpoint of further improving adhesion. The rare earth element oxide contained in the corrosion-resistant film can be used alone or in combination of two or more. Examples of the liquid dispersion medium for the rare earth element oxide sol include various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents, and water is preferred. As the cationic polymer, for example, polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or its derivative, aminated phenol, etc. are preferable. In addition, as the anionic polymer, poly(meth)acrylic acid or its salt, or a copolymer mainly composed of (meth)acrylic acid or its salt, is preferable. In addition, it is preferable that the crosslinking agent is at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. In addition, it is preferable that the phosphoric acid or the phosphoric acid salt is a condensed phosphoric acid or a condensed phosphate salt.
[0078] One example of a corrosion-resistant coating is one formed by applying a solution of fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate dispersed in phosphoric acid to the surface of a barrier layer and baking the coating at 150°C or higher.
[0079] If necessary, the corrosion-resistant coating may have a laminated structure in which at least one of a cationic polymer and an anionic polymer is further laminated. Examples of the cationic polymer and anionic polymer include those mentioned above.
[0080] The composition of the corrosion-resistant film can be analyzed by, for example, time-of-flight secondary ion mass spectrometry.
[0081] The amount of the corrosion-resistant film formed on the surface of the barrier layer 3 in the chemical conversion treatment is not particularly limited. For example, in the case of coating-type chromate treatment, the amount of the corrosion-resistant film formed on the surface of the barrier layer 3 is preferably 1 mm. 2 For example, the amount of the chromate compound is about 0.5 to 50 mg, preferably 1 It is desirable that the content of the phosphorus compound is, for example, about 0.5 to 50 mg, preferably about 1.0 to 40 mg, in terms of phosphorus, and the aminated phenol polymer is, for example, about 1.0 to 200 mg, preferably about 5.0 to 150 mg.
[0082] The thickness of the corrosion-resistant film is not particularly limited, but is preferably about 1 nm to 20 μm, more preferably about 1 nm to 100 nm, and even more preferably about 1 nm to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the barrier layer and the heat-sealable resin layer. The thickness of the corrosion-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy. Analysis of the composition of the corrosion-resistant film using time-of-flight secondary ion mass spectrometry can reveal that, for example, secondary ions consisting of Ce, P, and O (e.g., Ce2PO4 + , C ePO4 - At least one of the following: CrPO2 + , CrPO4 - Peaks derived from at least one of the above are detected.
[0083] The chemical conversion treatment is carried out by applying a solution containing a compound used for forming a corrosion-resistant film to the surface of the barrier layer by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the barrier layer so that the temperature of the barrier layer becomes about 70 to 200°C. In addition, before applying the chemical conversion treatment to the barrier layer, the barrier layer may be subjected to a degreasing treatment by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, it becomes possible to carry out the chemical conversion treatment of the surface of the barrier layer more efficiently. In addition, by using an acid degreasing agent in which a fluorine-containing compound is dissolved in an inorganic acid for the degreasing treatment, it is possible to not only degrease the metal foil but also form a fluoride of the metal that is in a passive state, and in such a case, only the degreasing treatment may be carried out.
[0084] [Thermofusible resin layer 4] In the exterior packaging material for an electricity storage device of the present disclosure, the heat-sealable resin layer 4 corresponds to the innermost layer and is a layer (sealant layer) that exhibits the function of sealing the electricity storage device elements by heat-sealing the heat-sealable resin layers to each other when the electricity storage device is assembled.
[0085] The resin constituting the heat-sealable resin layer 4 is not particularly limited as long as it is heat-sealable, but is preferably a resin containing a polyolefin skeleton, such as polyolefin or acid-modified polyolefin. The inclusion of a polyolefin skeleton in the resin constituting the heat-sealable resin layer 4 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like. Furthermore, when the resin constituting the heat-sealable resin layer 4 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride is detected at a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the peak. When the thermally adhesive resin layer 4 is a layer composed of maleic anhydride-modified polyolefin, a peak derived from maleic anhydride is detected by infrared spectroscopy. However, if the degree of acid modification is low, the peak becomes small and may not be detected. In that case, analysis can be performed by nuclear magnetic resonance spectroscopy.
[0086] Specific examples of polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); propylene-α-olefin copolymers; and ethylene-butene-propylene terpolymers. Among these, polypropylene is preferred. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more.
[0087] The polyolefin may be a cyclic polyolefin. The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, styrene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; and cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these, cyclic alkenes are preferred, and norbornene is more preferred.
[0088] The acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of a polyolefin with an acid component. The polyolefin to be modified with an acid may be the above-mentioned polyolefin, a copolymer obtained by copolymerizing the above-mentioned polyolefin with a polar molecule such as acrylic acid or methacrylic acid, or a polymer such as a crosslinked polyolefin. The acid component used for the acid modification may be, for example, a carboxylic acid or an anhydride such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, or itaconic anhydride.
[0089] The acid-modified polyolefin may be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin by replacing it with an acid component, or by block-polymerizing or graft-polymerizing an acid component to the cyclic polyolefin. The cyclic polyolefin to be acid-modified is the same as described above. The acid component used for the acid modification may be the same as that of the polyolefin described above. The acid components are similar to those used in the modification of vinyl ether.
[0090] Preferred acid-modified polyolefins include polyolefins modified with a carboxylic acid or anhydride thereof, polypropylenes modified with a carboxylic acid or anhydride thereof, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.
[0091] The thermally adhesive resin layer 4 may be formed of one type of resin alone, or may be formed of a blend polymer of two or more types of resins. Furthermore, the thermally adhesive resin layer 4 may be formed of only one layer, or may be formed of two or more layers of the same or different resins.
[0092] The heat-sealable resin layer 4 may contain a lubricant, etc., if necessary. When the heat-sealable resin layer 4 contains a lubricant, the moldability of the exterior material for a power storage device can be improved. The lubricant is not particularly limited, and a known lubricant can be used. The lubricant may be used alone or in combination of two or more kinds.
[0093] The lubricant is not particularly limited, but preferably includes an amide-based lubricant. Specific examples of the lubricant include those exemplified for the base layer 1. The lubricant may be used alone or in combination of two or more kinds.
[0094] When a lubricant is present on the surface of the heat-sealable resin layer 4, the amount of the lubricant is not particularly limited. From the viewpoint of improving the formability of the exterior material for an electrical storage device, the amount of the lubricant is preferably 10 to 50 mg / m 2 about 15 to 40 mg / m 2 The degree of
[0095] The lubricant present on the surface of the heat-fusible resin layer 4 may be a lubricant exuded from the resin constituting the heat-fusible resin layer 4, or a lubricant applied to the surface of the heat-fusible resin layer 4.
[0096] The thickness of the heat-sealable resin layer 4 is not particularly limited as long as the heat-sealable resin layers are heat-sealed to each other to exhibit the function of sealing the electricity storage device element, and may be, for example, about 100 μm or less, preferably about 85 μm or less, and more preferably about 15 to 85 μm. For example, when the thickness of the adhesive layer 5 described below is 10 μm or more, the thickness of the heat-sealable resin layer 4 is preferably about 85 μm or less, and more preferably about 15 to 45 μm. For example, when the thickness of the adhesive layer 5 described below is less than 10 μm or when the adhesive layer 5 is not provided, the thickness of the heat-sealable resin layer 4 is preferably about 20 μm or more, and more preferably about 35 to 85 μm.
[0097] [Adhesive layer 5] In the packaging material for an electricity storage device of the present disclosure, the adhesive layer 5 is a layer that is provided, if necessary, between the barrier layer 3 (or the corrosion-resistant film) and the heat-sealable resin layer 4 in order to firmly bond them together.
[0098] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-sealable resin layer 4. The resin used to form the adhesive layer 5 may be, for example, the same adhesive as exemplified for the adhesive layer 2. The resin used to form the adhesive layer 5 preferably contains a polyolefin skeleton, and examples thereof include the polyolefin and acid-modified polyolefin exemplified for the heat-sealable resin layer 4. The inclusion of a polyolefin skeleton in the resin constituting the adhesive layer 5 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. In addition, when the resin constituting the adhesive layer 5 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride at a wave number of 1760 cm is detected. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.
[0099] From the viewpoint of firmly adhering the barrier layer 3 and the heat-fusible resin layer 4, the adhesive layer 5 preferably contains an acid-modified polyolefin. Particularly preferred examples of the acid-modified polyolefin include polyolefins modified with carboxylic acid or its anhydride, polypropylenes modified with carboxylic acid or its anhydride, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.
[0100] Furthermore, from the viewpoint of reducing the thickness of the electrical storage device exterior material while providing an electrical storage device exterior material with excellent shape stability after molding, the adhesive layer 5 is more preferably a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. Preferred examples of the acid-modified polyolefin include those mentioned above.
[0101] The adhesive layer 5 is preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group and a compound having an epoxy group. The adhesive layer 5 is preferably at least one selected from the group consisting of polyurethane, polyester, and epoxy resin, and more preferably contains polyurethane and epoxy resin. As the polyester, for example, an amide ester resin is preferable. Amide ester resins are generally produced by the reaction of a carboxyl group and an oxazoline group. The adhesive layer 5 is more preferably a cured product of a resin composition containing at least one of these resins and the acid-modified polyolefin. In addition, if unreacted compounds such as a compound having an isocyanate group, a compound having an oxazoline group, or a curing agent such as an epoxy resin remain in the adhesive layer 5, the presence of the unreacted compounds can be confirmed by a method selected from, for example, infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.
[0102] In addition, from the viewpoint of further increasing the adhesion between the barrier layer 3 and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent having at least one selected from the group consisting of an oxygen atom, a heterocycle, a C=N bond, and a COC bond. Examples of the curing agent having a heterocycle include a curing agent having an oxazoline group and a curing agent having an epoxy group. Examples of the curing agent having a C=N bond include a curing agent having an oxazoline group and a curing agent having an isocyanate group. Examples of the curing agent having a COC bond include a curing agent having an oxazoline group, a curing agent having an epoxy group, and polyurethane. It can be confirmed that the adhesive layer 5 is a cured product of a resin composition containing these curing agents by, for example, gas chromatography mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS), or other methods.
[0103] The compound having an isocyanate group is not particularly limited, but from the viewpoint of effectively increasing the adhesion between the barrier layer 3 and the adhesive layer 5, a polyfunctional isocyanate compound is preferably used. The polyfunctional isocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of polyfunctional isocyanate-based curing agents include pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers. In addition, adducts, biuret products, isocyanurates, etc. are also included.
[0104] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0105] The compound having an oxazoline group is not particularly limited as long as it is a compound having an oxazoline skeleton. Specific examples of the compound having an oxazoline group include those having a polystyrene main chain and those having an acrylic main chain. In addition, examples of commercially available products include the Epocross series manufactured by Nippon Shokubai Co., Ltd.
[0106] The proportion of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0107] An example of a compound having an epoxy group is an epoxy resin. The epoxy resin is not particularly limited as long as it is a resin capable of forming a crosslinked structure by the epoxy group present in the molecule, and a known epoxy resin can be used. The weight average molecular weight of the epoxy resin is preferably about 50 to 2000, more preferably about 100 to 1000, and further preferably about 200 to 800. In the first disclosure, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under conditions using polystyrene as a standard sample.
[0108] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, polyglycerin polyglycidyl ether, etc. The epoxy resins may be used alone or in combination of two or more.
[0109] The ratio of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0110] The polyurethane is not particularly limited, and any known polyurethane can be used. The adhesive layer 5 may be, for example, a cured product of a two-component curing polyurethane.
[0111] The proportion of polyurethane in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5 in an atmosphere containing a component that induces corrosion of the barrier layer, such as an electrolyte solution.
[0112] In addition, when the adhesive layer 5 is a cured product of a resin composition containing at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and an epoxy resin, and the acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group, and the compound having an epoxy group each function as a curing agent.
[0113] The upper limit of the thickness of the adhesive layer 5 is preferably about 50 μm or less, about 40 μm or less, about 30 μm or less, about 20 μm or less, and about 5 μm or less, and the lower limit is preferably about 0.1 μm or more, and about 0.5 μm or more, and the thickness range is preferably about 0.1 to 50 μm, about 0.1 to 40 μm, about 0.1 to 30 μm, about 0.1 to 20 μm, about 0.1 to 5 μm, about 0.5 to 50 μm, about 0.5 to 40 μm, about 0.5 to 30 μm, about 0.5 to 20 μm, and about 0.5 to 5 μm. More specifically, in the case of the adhesive exemplified in the adhesive layer 2 or a cured product of an acid-modified polyolefin and a curing agent, the thickness is preferably about 1 to 10 μm, and more preferably about 1 to 5 μm. When a resin exemplified for the heat-fusible resin layer 4 is used, the thickness is preferably about 2 to 50 μm, more preferably about 10 to 40 μm. When the adhesive layer 5 is an adhesive exemplified for the adhesive layer 2 or a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed, for example, by applying the resin composition and curing it by heating or the like. When a resin exemplified for the heat-fusible resin layer 4 is used, the adhesive layer 5 can be formed, for example, by extrusion molding the heat-fusible resin layer 4 and the adhesive layer 5.
[0114] [Surface coating layer 6] The exterior material for an electricity storage device according to the present disclosure may have a surface coating layer 6 on the substrate layer 1 (the opposite side of the substrate layer 1 to the barrier layer 3) as necessary, for the purpose of improving at least one of design, electrolyte resistance, scratch resistance, formability, etc. The surface coating layer 6 is a layer located on the outermost layer side of the exterior material for an electricity storage device when an electricity storage device is assembled using the exterior material for an electricity storage device.
[0115] The surface coating layer 6 can be formed from a resin such as polyvinylidene chloride, polyester, polyurethane, acrylic resin, or epoxy resin.
[0116] When the resin forming the surface coating layer 6 is a curable resin, the resin may be either a one-component curable type or a two-component curable type, but is preferably a two-component curable type. Examples of two-component curable resins include two-component curable polyurethane, two-component curable polyester, and two-component curable epoxy resin. Among these, two-component curable polyurethane is preferred.
[0117] Examples of two-component curing polyurethane include polyurethanes containing a base material containing a polyol compound and a curing agent containing an isocyanate compound. Preferably, two-component curing polyurethanes are used in which a polyol such as polyester polyol, polyether polyol, and acrylic polyol is used as a base material, and an aromatic or aliphatic polyisocyanate is used as a curing agent. In addition, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the terminal hydroxyl group of the repeating unit as the polyol compound. Since the surface coating layer 6 is formed of polyurethane, excellent electrolyte resistance is imparted to the exterior material for the electricity storage device.
[0118] The surface coating layer 6 may contain additives such as the above-mentioned lubricant, antiblocking agent, matting agent, flame retardant, antioxidant, tackifier, and antistatic agent in at least one of the surface and the inside of the surface coating layer 6, as necessary, depending on the functionality to be provided to the surface of the surface coating layer 6. Examples of the additives include fine particles having an average particle size of about 0.5 nm to 5 μm. The average particle size of the additive is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0119] The additive may be either inorganic or organic. The shape of the additive is not particularly limited, and examples of the shape include spherical, fibrous, plate-like, amorphous, and scaly.
[0120] Specific examples of additives include talc, silica, graphite, kaolin, montmorillonite, mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, alumina, carbon black, carbon nanotubes, high melting point nylon, acrylate resin, crosslinked acrylic, crosslinked styrene, crosslinked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. The additives may be used alone or in combination of two or more. Among these additives, silica, barium sulfate, and titanium oxide are preferable from the viewpoint of dispersion stability and cost. In addition, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment.
[0121] The method for forming the surface coating layer 6 is not particularly limited, and examples thereof include a method for applying a resin that forms the surface coating layer 6. When an additive is blended into the surface coating layer 6, a resin mixed with the additive may be applied.
[0122] The thickness of the surface coating layer 6 is not particularly limited as long as the surface coating layer 6 exhibits the above-mentioned functions, and may be, for example, about 0.5 to 10 μm, and preferably about 1 to 5 μm.
[0123] 3. Manufacturing method for exterior material for power storage device The method for producing an exterior material for an electricity storage device is not particularly limited as long as a laminate is obtained by laminating the layers of the exterior material for an electricity storage device of the present disclosure, and examples thereof include a method including a step of laminating, from the outside, at least a base material layer 1, a barrier layer 3, and a heat-sealable resin layer 4 in this order. Specifically, the method for producing an exterior material for an electricity storage device of the present disclosure includes a step of obtaining a laminate in which, from the outside, at least a base material layer, a barrier layer, and a heat-sealable resin layer are laminated, the base material layer includes a polyamide film, and the crystallization index of the polyamide film measured from the outside of the base material layer by the ATR method of Fourier transform infrared spectroscopy is 1.50 or more.
[0124] An example of a method for producing an exterior material for an electricity storage device according to the present disclosure is as follows. First, a laminate (hereinafter, sometimes referred to as "laminate A") is formed in which a base layer 1, an adhesive layer 2, and a barrier layer 3 are laminated in this order. Specifically, the laminate A can be formed by a dry lamination method in which an adhesive used for forming the adhesive layer 2 is applied to the base layer 1 or to the barrier layer 3, the surface of which has been chemically treated as necessary, by a coating method such as gravure coating or roll coating, and then dried, and the barrier layer 3 or base layer 1 is laminated thereon, and the adhesive layer 2 is cured.
[0125] Next, the heat-sealable resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-sealable resin layer 4 is directly laminated on the barrier layer 3, the heat-sealable resin layer 4 may be laminated on the barrier layer 3 of the laminate A by a method such as thermal lamination or extrusion lamination. When an adhesive layer 5 is provided between the barrier layer 3 and the heat-sealable resin layer 4, for example, (1) a method of laminating the adhesive layer 5 and the heat-sealable resin layer 4 by extruding them on the barrier layer 3 of the laminate A (co-extrusion lamination method, tandem lamination method), (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-sealable resin layer 4 are laminated, and laminating this on the barrier layer 3 of the laminate A by a thermal lamination method, or a method of forming a laminate in which the adhesive layer 5 is laminated on the barrier layer 3 of the laminate A, and laminating this on the heat-sealable resin layer 4 by a thermal lamination method. (3) a method in which a molten adhesive layer 5 is poured between the barrier layer 3 of the laminate A and a heat-sealable resin layer 4 previously formed into a sheet-like film, and the laminate A and the heat-sealable resin layer 4 are bonded together via the adhesive layer 5 (sandwich lamination method); (4) a method in which an adhesive for forming an adhesive layer 5 is solution-coated on the barrier layer 3 of the laminate A, and laminated by drying or baking, and then the heat-sealable resin layer 4 previously formed into a sheet-like film is laminated on the adhesive layer 5.
[0126] When the surface coating layer 6 is provided, the surface coating layer 6 is laminated on the surface of the base layer 1 opposite to the barrier layer 3. The surface coating layer 6 can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer 6 to the surface of the base layer 1. The order of the step of laminating the barrier layer 3 on the surface of the base layer 1 and the step of laminating the surface coating layer 6 on the surface of the base layer 1 is not particularly limited. For example, after forming the surface coating layer 6 on the surface of the base layer 1, the barrier layer 3 may be formed on the surface of the base layer 1 opposite to the surface coating layer 6.
[0127] As described above, a laminate is formed comprising, from the outside, an optional surface coating layer 6 / a substrate layer 1 / an optional adhesive layer 2 / a barrier layer 3 / an optional adhesive layer 5 / a heat-sealable resin layer 4. In order to strengthen the adhesion of the optional adhesive layer 2 and adhesive layer 5, the laminate may be subjected to a heat treatment.
[0128] In the exterior packaging material for an electricity storage device, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary, to improve the processability. For example, by subjecting the surface of the base layer 1 opposite to the barrier layer 3 to corona treatment, the printability of the ink on the surface of the base layer 1 can be improved.
[0129] 4. Applications of exterior materials for energy storage devices The exterior material for an electricity storage device according to the present disclosure is used in a package for hermetically housing an electricity storage device element such as a positive electrode, a negative electrode, an electrolyte, etc. That is, an electricity storage device can be formed by housing an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte in a package formed from the exterior material for an electricity storage device according to the present disclosure.
[0130] Specifically, an electricity storage device element having at least a positive electrode, a negative electrode, and an electrolyte is covered with the exterior material for an electricity storage device of the present disclosure in such a manner that a flange portion (a region where the heat-sealable resin layers contact each other) can be formed on the periphery of the electricity storage device element with the metal terminals connected to each of the positive electrode and the negative electrode protruding outward, and the heat-sealable resin layers of the flange portion are heat-sealed to provide an electricity storage device using the exterior material for an electricity storage device. When an electricity storage device element is housed in a package formed with the exterior material for an electricity storage device of the present disclosure, the package is formed so that the heat-sealable resin portion of the exterior material for an electricity storage device of the present disclosure faces inside (the surface in contact with the electricity storage device element).
[0131] The exterior material for an electric storage device of the present disclosure can be suitably used for an electric storage device such as a battery (including a condenser, a capacitor, etc.). The exterior material for an electric storage device of the present disclosure may be used for either a primary battery or a secondary battery, but is preferably a secondary battery. The type of secondary battery to which the exterior material for an electric storage device of the present disclosure is applied is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, all-solid-state batteries, lead-acid batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among these secondary batteries, examples of suitable applications of the exterior material for an electric storage device of the present disclosure include lithium ion batteries and lithium ion polymer batteries.
[0132] An electricity storage device is generally fixed to the housing of various products via double-sided tape or adhesive. That is, the exterior material 10 for an electricity storage device according to the present disclosure is fixed to the housing of various products via double-sided tape or adhesive. The material of the housing varies depending on the type of product, and includes a wide range of materials, such as metals such as stainless steel, aluminum alloy, and nickel alloy, plastics such as polyolefin, polyamide, polyester, polyimide, and polystyrene, and glass.
[0133] The adhesive strength between the electricity storage device and the housing is adjusted, for example, to such an extent that the electricity storage device can be peeled off from the housing. The peel strength between the electricity storage device and the housing is preferably fixed using a double-sided tape that has a peel strength against a stainless steel plate of about 5 to 15 N / 7.5 mm as measured in (Measurement of Peel Strength of Double-Sided Tape) described below. The exterior material 10 for an electricity storage device can be suitably used for an electricity storage device that is fixed to a housing using a double-sided tape that has a peel strength against the housing of about 5 to 15 N / 7.5 mm.
[0134] 5. Polyamide film The polyamide film of the present disclosure is a polyamide film for use in a base layer of an electrical storage device packaging material composed of a laminate including at least a base layer, a barrier layer, and a heat-sealable resin layer, and has a crystallization index of 1.50 or more as measured by the ATR method of Fourier transform infrared spectroscopy. Details of the electrical storage device packaging material 10 are as described above.
[0135] By using the polyamide film of the present disclosure as the base layer 1 of the exterior material for an electric storage device, the crystallization index of the polyamide film of the base layer 1 of the exterior material for an electric storage device 10 can be suitably set to 1.50 or more, and the damage of the exterior material for an electric storage device during the above-mentioned peeling can be effectively suppressed. That is, it is preferable to manufacture the exterior material for an electric storage device 10 of the present disclosure by using the polyamide film of the present disclosure, the crystallization index of which has been adjusted to 1.50 or more in advance, as the base layer 1 and laminating it with each layer such as the barrier layer 3 and the heat-sealable resin layer 4. As described above, the crystallization index of the polyamide film laminated on the exterior material for an electric storage device 10 and included in the base layer 1 can be increased compared to the polyamide film before being applied to the exterior material for an electric storage device 10. Specifically, the crystallization index can also be increased by applying heat to the polyamide film during the manufacturing process of the exterior material for an electric storage device 10.
[0136] For the polyamide films of the present disclosure, the method for measuring the Crystallization Index is as follows.
[0137] <Measurement of the crystallization index of polyamide film> The polyamide film is cut into a 100 mm × 100 mm square to prepare a sample. The surface of the obtained sample is subjected to infrared absorption spectrum measurement in an environment of a temperature of 25°C and a relative humidity of 50% using an FT-IR in ATR measurement mode. For example, a Nicolet iS10 manufactured by Thermo Fisher Scientific Co., Ltd. can be used as the apparatus. From the obtained absorption spectrum, a 1200 cm -1 The peak intensity P near 1370 cm originates from absorption unrelated to crystals.-1 The peak intensity Q in the vicinity is measured, and the intensity ratio X=P / Q of the peak intensity P to the peak intensity Q is calculated as the crystallization index. (Measurement conditions) Method: Macro ATR method Wavenumber resolution: 8cm -1 Number of times: 32 Detector: DTGS detector ATR prism: Ge Incident angle: 45° Baseline: Wave number 1100cm -1 From 1400cm -1 The curve was calculated as a straight line approximation between the two. Absorption peak intensity Y 1200 : Wave number 1195cm -1 From 1205cm -1 The maximum peak intensity in the range minus the baseline value Absorption peak intensity Y 1370 : Wave number 1365cm -1 From 1375cm -1 The maximum peak intensity in the range minus the baseline value
[0138] In the polyamide film of the present disclosure, the crystallization index may be 1.50 or more, but from the viewpoint of more effectively suppressing damage to the electrical storage device packaging material during the above-mentioned peeling, it is more preferably 1.55 or more, even more preferably 1.60 or more, and particularly preferably 1.65 or more. The upper limit of the crystallization index is not particularly limited, but may be, for example, 2.50 or less, 1.80 or less, etc. Preferred ranges of the crystallization index include, for example, 1.50 to 2.50, 1.60 to 2.50, 1.65 to 2.50, 1.50 to 1.80, 1.60 to 1.80, and 1.65 to 1.80.
[0139] Specific examples of polyamides forming the polyamide film are as described in the section on the base layer 1 of the exterior material 10 for a power storage device. The polyamide film may be an unstretched film or a stretched film. Examples of stretched films include uniaxially stretched films and biaxially stretched films, with biaxially stretched films being preferred. Examples of stretching methods for forming biaxially stretched films include sequential biaxial stretching, inflation, and simultaneous biaxial stretching. Examples of methods for applying a resin include roll coating, gravure coating, and extrusion coating.
[0140] The polyamide film is preferably a biaxially oriented nylon film.
[0141] The thickness of the polyamide film is, from the viewpoint of more effectively preventing damage to the exterior material for an electricity storage device during the aforementioned peeling, preferably about 3 μm or more, more preferably about 10 μm or more, and is also preferably about 50 μm or less, more preferably about 35 μm or less. Preferred ranges include about 3 to 50 μm, about 3 to 35 μm, about 10 to 50 μm, and about 10 to 35 μm, and of these, about 10 to 35 μm is particularly preferred.
[0142] Additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present on at least one of the surface and the interior of the polyamide film. Only one type of additive may be used, or two or more types may be mixed and used. Details of the additives are as described in the section on the base layer 1 of the exterior material 10 for an electricity storage device. EXAMPLES
[0143] The present disclosure will be described in detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the examples.
[0144] <Manufacture of exterior materials for power storage devices> Examples 1-3 and Comparative Examples 1-2 As the substrate layer, a stretched nylon (ONy) film (thickness 25 μm) was prepared. As described later, the stretched nylon films used in Examples 1-3 and Comparative Examples 1-2 were adjusted to the crystallization index values shown in Table 1 by changing the stretch ratio and heat setting temperature. The stretched nylon film was coated with erucic acid amide as a lubricant. As the barrier layer, an aluminum alloy foil (JIS H4160:1994 A8021H-O (thickness 40 μm)) was prepared. Next, an adhesive (two-liquid urethane adhesive) was applied to one side of the aluminum alloy foil and dried. Next, the adhesive on the barrier layer and the substrate layer were laminated by a dry lamination method, and then aging treatment was performed to produce a substrate layer (thickness 25 μm) / adhesive layer (thickness 3 μm after curing) / barrier layer (thickness 40 μm). Both sides of the aluminum alloy foil were subjected to a chemical conversion treatment. The chemical conversion treatment of aluminum alloy foil is carried out using a treatment solution consisting of phenolic resin, chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m 2 (dry weight) of aluminum alloy foil by roll coating method. This was done by coating on both sides and baking.
[0145] Next, maleic anhydride modified polypropylene as an adhesive layer (thickness 23 μm) and random polypropylene as a heat-sealable resin layer (thickness 23 μm) were co-extruded onto the barrier layer of each of the laminates obtained above, thereby laminating the adhesive layer / heat-sealable resin layer on top of the barrier layer, and aging was performed to obtain a laminate (total thickness 114 μm) in which, from the outside, the base layer (thickness 25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (23 μm) / heat-sealable resin layer (23 μm) were laminated.
[0146] Example 4 As the substrate layer, a stretched nylon (ONy) film (thickness 20 μm) was prepared. As described later, the stretched nylon film used in Example 4 was adjusted to the crystallization index value shown in Table 1 by changing the stretch ratio and heat setting temperature. The stretched nylon film had a coating layer (a polyester polyurethane containing a lubricant applied to a thickness of 300 nm or less) on the surface opposite to the barrier layer, and a coating layer (a polyester polyurethane applied to a thickness of 300 nm or less) on the surface on the barrier layer side. As the barrier layer, an aluminum alloy foil (JIS H4160:1994 A8021H-O (thickness 35 μm)) was prepared. Next, an adhesive (two-liquid urethane adhesive) was applied to one side of the aluminum alloy foil and dried. Next, the adhesive on the barrier layer and the substrate layer were laminated by a dry lamination method, and then aging treatment was performed to produce a substrate layer (thickness 20 μm) / adhesive layer (thickness 3 μm after curing) / barrier layer (thickness 35 μm). Both sides of the aluminum alloy foil are treated with a chemical conversion coating. The chemical conversion coating of the aluminum alloy foil is performed by applying a treatment solution consisting of phenolic resin, chromium fluoride compound, and phosphoric acid at a coating amount of 10 mg / m 2 (dry quality The coating was applied to both sides of the aluminum alloy foil by roll coating so that the coating amount became 100%. Then, the coating was baked.
[0147] Next, maleic anhydride modified polypropylene as an adhesive layer (thickness 15 μm) and random polypropylene as a heat-sealable resin layer (thickness 15 μm) were co-extruded onto the barrier layer of each of the laminates obtained above, thereby laminating the adhesive layer / heat-sealable resin layer on top of the barrier layer, and aging was performed to obtain a laminate (total thickness 88 μm) in which, from the outside, the base layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (35 μm) / adhesive layer (15 μm) / heat-sealable resin layer (15 μm) were laminated.
[0148] Example 5 As the substrate layer, a stretched nylon (ONy) film (thickness 20 μm) was prepared. The stretched nylon film used in Example 5 was the same as that used in Example 4. The stretched nylon film had a coating layer (a polyester polyurethane containing a lubricant applied to a thickness of 300 nm or less) on the surface opposite to the barrier layer, and a coating layer (a polyester polyurethane applied to a thickness of 300 nm or less) on the surface on the barrier layer side. An aluminum alloy foil (JIS H4160:1994 A8021H-O (thickness 30 μm)) was prepared as the barrier layer. Next, an adhesive (two-liquid urethane adhesive) was applied to one side of the aluminum alloy foil and dried. Next, the adhesive on the barrier layer and the substrate layer were laminated by a dry lamination method, and then aging treatment was performed to produce a laminate of substrate layer (thickness 20 μm) / adhesive layer (thickness 3 μm after curing) / barrier layer (thickness 30 μm). Both sides of the aluminum alloy foil were subjected to a chemical conversion treatment. The chemical conversion treatment of aluminum alloy foil is carried out using a treatment solution consisting of phenolic resin, chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m 2 (dry weight) was applied to both sides of an aluminum alloy foil by roll coating, and then baked.
[0149] Next, maleic anhydride modified polypropylene as an adhesive layer (thickness 14 μm) and random polypropylene as a heat-sealable resin layer (thickness 10 μm) were co-extruded onto the barrier layer of each of the laminates obtained above, thereby laminating the adhesive layer / heat-sealable resin layer on top of the barrier layer, and aging was performed to obtain a laminate (total thickness 77 μm) in which, from the outside, the base layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (30 μm) / adhesive layer (14 μm) / heat-sealable resin layer (10 μm) were laminated.
[0150] Example 6 A laminate (total thickness 114 μm) was obtained in the same manner as in Example 1, except that a stretched nylon (ONy) film having a coating layer (polyester polyurethane applied to a thickness of 300 nm or less) on the surface on the barrier layer side was used as the base layer, and the laminate was composed of, from the outside, a base layer (thickness 25 μm), an adhesive layer (3 μm), a barrier layer (40 μm), an adhesive layer (23 μm), and a heat-sealable resin layer (23 μm).
[0151] Example 7 As the substrate layer, an oriented nylon (ONy) film (thickness 20 μm) was prepared. The oriented nylon film used in Example 7 was the same as that used in Example 4. As the barrier layer, an aluminum alloy foil (JIS H4160:1994 A8021H-O (thickness 35 μm)) was prepared. Next, the barrier layer and the substrate layer were laminated by a dry lamination method using an adhesive (a two-liquid urethane adhesive containing carbon black), and then aging treatment was performed to produce a substrate layer (thickness 20 μm) / adhesive layer (thickness 3 μm after curing) / barrier layer (thickness 35 μm). Both sides of the aluminum alloy foil were subjected to chemical conversion treatment. The chemical conversion treatment of the aluminum alloy foil was performed using a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m. 2 (dry mass) The coating was applied to both sides of an aluminum alloy foil by roll coating and then baked.
[0152] Next, maleic anhydride modified polypropylene as an adhesive layer (thickness 15 μm) and random polypropylene as a heat-sealable resin layer (thickness 15 μm) were co-extruded on the barrier layer of each of the laminates obtained above, thereby laminating the adhesive layer / heat-sealable resin layer on top of the barrier layer to obtain a laminate having a base layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (35 μm) / adhesive layer (15 μm) / heat-sealable resin layer (15 μm) laminated in that order. Next, a two-component urethane resin containing silica particles and resin beads was applied to the surface of the stretched nylon film of the obtained laminate to a thickness of 3 μm to form a matte layer as a surface coating layer, and aging was performed to obtain a laminate (total thickness 91 μm) consisting of, from the outside, a surface coating layer (thickness 3 μm) / base layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (35 μm) / adhesive layer (15 μm) / thermally adhesive resin layer (15 μm).
[0153] Example 8 As the substrate layer, an oriented nylon (ONy) film (thickness 20 μm) was prepared. The oriented nylon film used in Example 8 was the same as that used in Example 4. As the barrier layer, an aluminum alloy foil (JIS H4160:1994 A8021H-O (thickness 40 μm)) was prepared. Next, an adhesive (two-liquid urethane adhesive) was applied to one side of the aluminum alloy foil and dried. Next, the adhesive on the barrier layer and the substrate layer were laminated by a dry lamination method, and then aging treatment was performed to produce a substrate layer (thickness 20 μm) / adhesive layer (thickness 3 μm after curing) / barrier layer (thickness 40 μm). Both sides of the aluminum alloy foil were subjected to chemical conversion treatment. The chemical conversion treatment of the aluminum alloy foil was performed by using a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m. 2 (dry weight) by roll coating on both sides of the aluminum alloy foil. The coating was applied to the surface and baked.
[0154] Next, maleic anhydride modified polypropylene as an adhesive layer (thickness 14 μm) and random polypropylene as a heat-sealable resin layer (thickness 10 μm) were co-extruded onto the barrier layer of each of the laminates obtained above, thereby laminating the adhesive layer / heat-sealable resin layer on top of the barrier layer, and aging was performed to obtain a laminate (total thickness 87 μm) in which, from the outside, the base layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (14 μm) / heat-sealable resin layer (10 μm) were laminated.
[0155] Example 9 As the substrate layer, an oriented nylon (ONy) film (thickness 20 μm) was prepared. The oriented nylon film used in Example 9 was the same as that used in Example 4. As the barrier layer, an aluminum alloy foil (JIS H4160:1994 A8021H-O (thickness 40 μm)) was prepared. Next, the barrier layer and the substrate layer were laminated by a dry lamination method using an adhesive (a two-liquid urethane adhesive containing carbon black), and then aging treatment was performed to produce a substrate layer (thickness 20 μm) / adhesive layer (thickness 3 μm after curing) / barrier layer (thickness 40 μm). Both sides of the aluminum alloy foil were subjected to chemical conversion treatment. The chemical conversion treatment of the aluminum alloy foil was performed using a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m. 2 (dry mass) The coating was applied to both sides of an aluminum alloy foil by roll coating and then baked.
[0156] Next, maleic anhydride modified polypropylene as an adhesive layer (thickness 14 μm) and random polypropylene as a heat-sealable resin layer (thickness 10 μm) were co-extruded onto the barrier layer of each of the laminates obtained above, thereby laminating an adhesive layer / heat-sealable resin layer on top of the barrier layer, thereby obtaining a laminate in which the substrate layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (14 μm) / heat-sealable resin layer (10 μm) were laminated in that order. Next, a two-component urethane resin containing silica particles and resin beads was applied to the surface of the stretched nylon film of the obtained laminate to a thickness of 3 μm to form a matte layer as a surface coating layer, and aging was performed to obtain a laminate (total thickness 90 μm) consisting of, from the outside, a surface coating layer (thickness 3 μm) / base layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (14 μm) / thermally adhesive resin layer (10 μm).
[0157] Example 10 As the substrate layer, an oriented nylon (ONy) film (thickness 20 μm) was prepared. The oriented nylon film used in Example 10 was the same as that used in Example 4. As the barrier layer, an aluminum alloy foil (JIS H4160:1994 A8021H-O (thickness 40 μm)) was prepared. Next, an adhesive (two-liquid urethane adhesive) was applied to one side of the aluminum alloy foil and dried. Next, the adhesive on the barrier layer and the substrate layer were laminated by a dry lamination method, and then aging treatment was performed to produce a substrate layer (thickness 20 μm) / adhesive layer (thickness 3 μm after curing) / barrier layer (thickness 40 μm). Both sides of the aluminum alloy foil were subjected to chemical conversion treatment. The chemical conversion treatment of the aluminum alloy foil was performed by using a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m. 2 (dry weight) of aluminum alloy foil by roll coating method. This was done by coating on both sides and baking.
[0158] Next, maleic anhydride modified polypropylene as an adhesive layer (thickness 15 μm) and random polypropylene as a heat-sealable resin layer (thickness 15 μm) were co-extruded onto the barrier layer of each of the laminates obtained above, thereby laminating the adhesive layer / heat-sealable resin layer on top of the barrier layer, and aging was performed to obtain a laminate (total thickness 93 μm) in which, from the outside, the base layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (15 μm) / heat-sealable resin layer (15 μm) were laminated.
[0159] Example 11 As the substrate layer, an oriented nylon (ONy) film (thickness 20 μm) was prepared. The oriented nylon film used in Example 11 was the same as that used in Example 4. As the barrier layer, an aluminum alloy foil (JIS H4160:1994 A8021H-O (thickness 40 μm)) was prepared. Next, the barrier layer and the substrate layer were laminated by a dry lamination method using an adhesive (a two-liquid urethane adhesive containing carbon black), and then aging treatment was performed to produce a substrate layer (thickness 20 μm) / adhesive layer (thickness 3 μm after curing) / barrier layer (thickness 40 μm). Both sides of the aluminum alloy foil were subjected to chemical conversion treatment. The chemical conversion treatment of the aluminum alloy foil was performed using a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m. 2 (Dry mass) The coating was applied to both sides of the aluminum alloy foil by roll coating and then baked.
[0160] Next, maleic anhydride modified polypropylene as an adhesive layer (thickness 14 μm) and random polypropylene as a heat-sealable resin layer (thickness 10 μm) were co-extruded on the barrier layer of each of the laminates obtained above, thereby laminating an adhesive layer / heat-sealable resin layer on top of the barrier layer, thereby obtaining a laminate in which the substrate layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (15 μm) / heat-sealable resin layer (15 μm) were laminated in that order. Next, a two-component urethane resin containing silica particles and resin beads was applied to the surface of the stretched nylon film of the obtained laminate to a thickness of 3 μm to form a matte layer as a surface coating layer, and aging was performed to obtain a laminate (total thickness 96 μm) consisting of, from the outside, a surface coating layer (thickness 3 μm) / base layer (thickness 20 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (15 μm) / thermally adhesive resin layer (15 μm).
[0161] <Measurement of the crystallization index of the base material layer of the exterior material for power storage devices> The exterior material for the power storage device was cut into a square of 100 mm × 100 mm to prepare a sample. The surface of the stretched nylon film located on the outside of the obtained sample was subjected to infrared absorption spectrum measurement under an environment of a temperature of 25 ° C. and a relative humidity of 50% using the ATR measurement mode of Nicolet iS10 FT-IR manufactured by Thermo Fisher Scientific Co., Ltd. From the obtained absorption spectrum, a peak at 1200 cm originating from the absorption of α crystals of nylon was observed. -1 The peak intensity P near 1370 cm originates from absorption unrelated to crystals. -1 The peak intensity Q near the peak was measured, and the intensity ratio X=P / Q of the peak intensity P to the peak intensity Q was calculated as the crystallization index. For Examples 7, 9, and 11, the measurement was performed before the surface coating layer was applied. The results are shown in Table 1. (Measurement conditions) Method: Macro ATR method Wavenumber resolution: 8cm -1 Number of times: 32 Detector: DTGS detector ATR prism: Ge Incident angle: 45° Baseline: Wave number 1100cm -1 From 1400cm -1 The curve was calculated as a straight line approximation between the two. Absorption peak intensity Y 1200 : Wave number 1195cm -1 From 1205cm -1 The maximum peak intensity in the range minus the baseline value Absorption peak intensity Y 1370 : Wave number 1365cm -1 From 1375cm -1 The maximum peak intensity in the range minus the baseline value
[0162] <Measurement of Crystallization Index of Stretched Nylon Film> The stretched nylon film used in the base layer of the exterior material for the power storage device was cut into a 100 mm × 100 mm square to prepare a sample. The surface of the obtained sample was subjected to infrared absorption spectrum measurement at a temperature of 25 ° C and a relative humidity of 50% using the ATR measurement mode of Nicolet iS10 FT-IR manufactured by Thermo Fisher Scientific Co., Ltd. From the obtained absorption spectrum, a peak at 1200 cm originating from the absorption of α crystals of nylon was observed. -1 The peak intensity P near 1370 cm originates from absorption unrelated to crystals. -1 The peak intensity Q near the peak was measured, and the intensity ratio X=P / Q of the peak intensity P to the peak intensity Q was calculated as the crystallization index. The results are shown in Table 1. (Measurement conditions) Method: Macro ATR method Wavenumber resolution: 8cm -1 Number of times: 32 Detector: DTGS detector ATR prism: Ge Incident angle: 45° Baseline: Wave number 1100cm -1 From 1400cm -1 The curve was calculated as a straight line approximation between the two. Absorption peak intensity Y 1200 : Wave number 1195cm -1 From 1205cm -1The maximum peak intensity in the range minus the baseline value Absorption peak intensity Y 1370 : Wave number 1365cm -1 From 1375cm -1 The maximum peak intensity in the range minus the baseline value
[0163] <Electricity storage device peeling test> The peel test of the electricity storage device was carried out according to the following procedure. The procedure will be described with reference to Figs. 5 to 8. First, the procedure for preparing a sample used in the peel test of the electricity storage device will be described with reference to Fig. 5. As shown in Fig. 5a, the exterior material for the electricity storage device was cut into a rectangular shape with a length (MD) of 200 mm and a width (TD) of 90 mm. Next, using a molding die (female die) with an aperture of 55 mm (MD) x 32 mm (TD) and a molding die (male die) corresponding to this, the exterior material for the electricity storage device was cold-molded to a depth of 5.0 mm from the heat-sealable resin layer side at a position 15 mm away from the short side of the exterior material for the electricity storage device, to form a recess M (the area surrounded by the dashed line in Fig. 5a). Next, an acrylic plate with a length of 55 mm, a width of 32 mm, and a thickness of 5 mm was inserted into the recess M (Figs. 5b and 5c). Next, the molded exterior material for an electricity storage device was folded in half in the TD direction at the crease P (along the short side of the recess M) so that the recess M was on the inside (FIG. 5d). Next, along the periphery of the recess M, the overlapping parts of the heat-sealable resin layers were heat-sealed (190°C, 3 seconds, surface pressure 1 MPa) at three points along the MD and TD to seal the recess M (FIG. 5e). In FIG. 5e, the colored area S is the heat-sealed part. Next, as shown in FIG. 5f, the sample 12 used in the peel test of the electricity storage device was prepared by trimming the sample 12 to a size of 60 mm in length (MD) and 37 mm in width (TD) along the recess M. FIG. 6 shows a side view (FIG. 6a) and a plan view (FIG. 6b) of the sample 12.
[0164] Next, as shown in the schematic diagram of Fig. 7, three double-sided tapes (7.5 mm wide, 55 mm long) were attached to both ends and the center of the flat surface of sample 12 (the surface opposite to the surface on which the recesses M were formed) along the machine direction (MD). The peel strength of the double-sided tapes to the object was measured by the method described later.
[0165] Next, the sample 12 with the double-sided tape attached was attached to a stainless steel plate and cured in a 60°C environment for 24 hours. The stainless steel plate was used as a case for fixing the power storage device with the double-sided tape. Next, as shown in the schematic diagram of FIG. 8, the sample 12 was carefully peeled off from the stainless steel plate using a metal spatula, and the presence or absence of holes in the peeled sample 12 was visually confirmed, and the peel test of the power storage device was evaluated for each of three samples according to the following criteria. As shown in FIG. 8, the power storage device was peeled off by applying force from the lateral direction (TD) of the sample 12. The results are shown in Table 1. A: No holes were formed in all three samples. B: One or two samples had holes. C: All three samples had holes.
[0166] [Table 1]
[0167] The exterior materials for electricity storage devices of Examples 1 to 11 are composed of a laminate including, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, and the base layer includes a polyamide film, and the polyamide film has a crystallization index of 1.50 or more measured from the outside of the base layer by the ATR method of Fourier transform infrared spectroscopy. The polyamide film used in the base layer of the exterior materials for electricity storage devices of Examples 1 to 11 has a crystallization index of 1.50 or more measured by the ATR method of Fourier transform infrared spectroscopy. It is understood that the exterior materials for electricity storage devices of Examples 1 to 11 effectively suppress damage to the exterior materials for electricity storage devices when peeling off an electricity storage device fixed with a double-sided tape or the like from a housing.
[0168] The difference between the crystallization index measured for the base layer of the exterior material for a storage battery device and the crystallization index measured for the stretched nylon film is considered to be due to the aging of the exterior material for a storage battery device. The stretched nylon film used in Comparative Examples 1 and 2 has a crystallization index value significantly smaller than that of Examples 1 to 11, but the value measured after being used as the base layer of the exterior material for a storage battery device is significantly larger than the value measured in the state of the stretched nylon film. However, in Comparative Examples 1 and 2, the crystallization index of the polyamide film measured from the outside of the base layer could not be increased to 1.50 or more by aging the exterior material for a storage battery device, and the peel test evaluation of the electricity storage device was inferior to that of Examples 1 to 11.
[0169] (Measurement of peel strength of double-sided tape) The exterior materials for the power storage device of Examples 1 to 11 (length 15 mm x width 70 mm), the double-sided tape (length 7.5 mm x width 60 mm) used in the <Peel test of the power storage device>, aluminum foil (thickness 35 μm x length 15 mm x width 150 mm), the double-sided adhesive tape for fixing (length 5 mm x width 60 mm), and the acrylic plate (thickness 3 mm x length 50 mm x width 70 mm) were prepared. First, the surface of the stretched nylon film side of the exterior material for the power storage device (the surface of the coating layer on the stretched nylon film in Examples 4 and 5, and the surface of the surface coating layer on the stretched nylon film in Examples 7, 9, and 11) was bonded to one side of the double-sided tape, and aluminum foil was further bonded to the other side of the double-sided tape, and a 2 kg roller was rolled back and forth from above the aluminum foil to obtain a laminate P. Also, the acrylic plate was bonded to one side of the double-sided adhesive tape for fixing to obtain a laminate Q. Furthermore, the surface of the heat-fusible resin layer of the exterior material for a power storage device of the laminate P was attached to the other side of the fixing double-sided adhesive tape of the laminate Q, and pressed down by hand to obtain a laminate R in which an acrylic plate, a fixing double-sided adhesive tape, an exterior material for a power storage device, a double-sided tape, and an aluminum foil were laminated in this order, and this was used as a test sample M. The test sample M was stored in an environment at a temperature of 60° C. for 24 hours. Next, the surface of the stretched nylon film of the exterior material for a power storage device and the end of the double-sided tape were peeled off by about 1 mm to provide a trigger point for measuring the peel strength. Next, the acrylic plate of the test sample M was fixed, and the aluminum foil was pulled using a tensile tester (manufactured by Shimadzu Corporation, AG-Xplus (trade name)) under conditions of a pulling angle of 180°, a peeling speed of 300 mm / min, and a peeling distance of 50 mm or more, and peeled at the interface between the stretched nylon film surface of the exterior material for the power storage device and the double-sided tape (from the aforementioned trigger portion), and the average of the five peel strengths at peel distances of 10 mm, 20 mm, 30 mm, and 40 mm, and the maximum peel strength between 10 and 40 mm, was calculated to obtain the peel strength (peel strength of the double-sided tape to the stretched nylon film (N / 7.5 mm)). The results are shown in Table 2.
[0170] Next, a stainless steel plate (3 mm thick x 50 mm long x 70 mm wide) and a double-sided tape (7.5 mm long x 60 mm wide), as well as the above-mentioned aluminum foil (35 μm thick x 15 mm long x 150 mm wide) were prepared for use in the <Peel Test of Electricity Storage Device>. The surface of the stainless steel plate was bonded to one side of the double-sided tape, and aluminum foil was bonded to the other side of the double-sided tape. A 2 kg roller was rolled back and forth once on the aluminum foil to obtain a laminate, which was used as test sample N. Test sample N was stored in an environment at a temperature of 60° C. for 24 hours. Next, the end of the double-sided tape was peeled off from the surface of the stainless steel plate by about 1 mm to provide a trigger for measuring the peel strength. Next, the stainless steel plate of test sample N was fixed, and the aluminum foil was pulled using a tensile tester (Shimadzu Corporation, AG-Xplus (product name)) at a pulling angle of 180°, a peeling speed of 300 mm / min, and a peeling distance of 50 mm or more, and peeled at the interface between the stainless steel plate surface and the double-sided tape (from the aforementioned trigger portion), and the average of the five peel strengths at peel distances of 10 mm, 20 mm, 30 mm, and 40 mm, and the maximum peel strength between 10 and 40 mm, was calculated to obtain the peel strength (peel strength of the double-sided tape to the stainless steel plate (N / 7.5 mm)). The results are shown in Table 2.
[0171] [Table 2]
[0172] As is clear from the results shown in Table 2, the peel strength of the double-sided tape used in the <Power storage device peel test> was comparable to that of the stretched nylon film and the stainless steel plate.
[0173] As described above, the present disclosure provides the following aspects of the invention. Item 1. The device is composed of a laminate including, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, The substrate layer includes a polyamide film, An exterior material for an electricity storage device, wherein the polyamide film has a crystallization index of 1.50 or more as measured from the outside of the base layer by an ATR method of Fourier transform infrared spectroscopy. Item 2. The exterior material for an electricity storage device according to Item 1, further comprising an adhesive layer between the base layer and the barrier layer. Item 3. The packaging material for an electricity storage device according to Item 1 or 2, further comprising an adhesive layer between the barrier layer and the heat-sealable resin layer. Item 4. The method includes a step of obtaining a laminate in which at least a base layer, a barrier layer, and a heat-sealable resin layer are laminated in this order from the outside, The substrate layer includes a polyamide film, A method for producing an exterior material for an electricity storage device, wherein the polyamide film has a crystallization index of 1.50 or more as measured from the outside of the base layer by an ATR method of Fourier transform infrared spectroscopy. Item 5. An electricity storage device, in which an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte is housed in a package formed from the exterior material for an electricity storage device according to any one of Items 1 to 3. Item 6. A polyamide film for use in a base material layer of an exterior material for an electricity storage device, the base material layer being composed of a laminate including at least a base material layer, a barrier layer, and a heat-sealable resin layer, The polyamide film has a crystallization index of 1.50 or more as measured by an ATR method of Fourier transform infrared spectroscopy. [Explanation of symbols]
[0174] 1 Base material layer 2 Adhesive layer 3. Barrier layer 4 Heat-fusible resin layer 5 Adhesive layer 6 Surface coating layer 10. Exterior materials for power storage devices
Claims
1. The laminate includes, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, The base layer includes a polyamide film having a thickness of 10 μm or more and 35 μm or less, The substrate layer is a single layer, An exterior material for an electricity storage device, wherein the polyamide film has a crystallization index of 1.50 or more as measured from the outside of the base layer by an ATR method of Fourier transform infrared spectroscopy.
2. The exterior packaging material for an electricity storage device according to claim 1 , wherein the barrier layer has a thickness of 25 μm or more and 50 μm or less.
3. An adhesive layer is further provided between the barrier layer and the thermal adhesive resin layer, The exterior material for an electricity storage device according to claim 1 or 2, wherein the adhesive layer has a thickness of 0.1 μm or more and 20 μm or less.
4. The exterior packaging material for an electricity storage device according to any one of claims 1 to 3, wherein the heat-sealable resin layer has a thickness of 10 µm or more and 23 µm or less.
5. The exterior material for an electricity storage device according to any one of claims 1 to 4, further comprising an adhesive layer between the base layer and the barrier layer.
6. The packaging material for an electricity storage device according to any one of claims 1 to 5, further comprising an adhesive layer between the barrier layer and the heat-sealable resin layer.
7. The method includes a step of obtaining a laminate in which at least a base layer, a barrier layer, and a thermally adhesive resin layer are laminated in this order from the outside, The base layer includes a polyamide film having a thickness of 10 μm or more and 35 μm or less, The substrate layer is a single layer, A method for producing an exterior material for an electricity storage device, wherein the polyamide film has a crystallization index of 1.50 or more as measured from the outside of the base layer by an ATR method of Fourier transform infrared spectroscopy.
8. An electricity storage device, comprising: an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte; and the electricity storage device element is housed in a package formed from the exterior material for an electricity storage device according to any one of claims 1 to 6.
9. A polyamide film having a thickness of 10 μm or more and 35 μm or less for use as a base material layer of an exterior material for an electricity storage device, the base material layer being composed of a laminate including at least a base material layer, a barrier layer, and a heat-sealable resin layer, The substrate layer is a single layer, The polyamide film has a crystallization index of 1.50 or more as measured by an ATR method of Fourier transform infrared spectroscopy.
Citation Information
Patent Citations
Biaxially stretched nylon film, laminated film, laminated packaging material, battery, and method for producing biaxially stretched nylon film
JP2015051528A
Biaxially stretched nylon film, laminate film, laminate packaging material, and method for producing biaxially stretched nylon film
WO2014103785A1
Packaging material for battery, manufacturing method therefor, and battery
WO2018066670A1
Packaging material for battery, battery, production methods therefor, and method for improving printing suitability of ink for packaging material for battery
WO2019031611A1
Layered package material, outer package material for battery, and the battery
JP2008287971A